Impact of digital literacy and market orientation through e-commerce adoption on the MSME performance moderated by O2O business adoption - Umi Suryani; Sri Bramantoro Abdinagoro; Mts Arief Arief; M Hamsal (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
This study aims to examine the influence of digital literacy and market orientation on MSME performance mediated by E-commerce adoption with O2O Business as a Moderating variable. The population in this study are all MSMEs that have collaborated with E-Commerce. The sample in this study was obtained using a quota sampling technique, which only limited data acquisition to 100 MSMEs of E-Commerce partners. Data is obtained by distributing questionnaires to respondents through online.  The collected data is then analysed using Path analysis assisted by the Smart PLS application.  The result shows that Digital Literacy and Market Orientation have a significant positive effect on E-Commerce Adoption, then E- Commerce Adoption, Market Orientation and Digital Literacy have a significant positive effect on Performance MSMEs, Digital Literacy, Market Orientation and E-commerce adoption has a significant positive effect on MSME Performance moderated by O2O Business Adoption. Understanding of market orientation and digital literacy in running a business can have an impact on customer satisfaction which then has an impact on improving MSME performance. Researchers who want to review the topic in this study can conduct a correlation test on a larger scale to get a more detailed picture of the impact of digital literacy and market orientation on MSMEs and other sectors.